Metabolomics Reveals a 26-Membered Macrolactone Produced by Endophytic Colletotrichum spp. from Alcatrazes Island, Brazil - Takaki, Mirelle; Williams, David E.; Freire, Vitor F.; Sartori, Sérgio B.; Lira, Simone P.; Bizarria, Rodolfo [UNESP]; Rodrigues, Andre [UNESP]; Gonçalves Da Costa, Danielle R.; Amorim, Marcelo R.; Ferreira, Antonio G.; Andersen, Raymond J.; Linington, Roger G.; et al. (American Chemical Society (ACS), 2022)
Comparative metabolomics analysis of nonphytotoxic endophytic Colletotrichum spp. isolated from Anthurium alcatrazense endemic to Alcatrazes island (Brazil) and phytopathogenic Colletotrichum spp. isolated from the mainland of Brazil revealed significant differences in chemical composition. Examination of endophytic Colletotrichum spp. from Alcatrazes island led to the discovery of a 26-member macrolactone, colletotrichumolide (1), containing a phosphatidyl choline side chain. Further examination of the phytopathogenic strains from the mainland identified a family of phytopathogenic metabolites not present in the nonpathogenic island-derived strains, suggesting that geographical isolation could influence the secondary metabolism of fungal strains.